2023
DOI: 10.1109/lgrs.2023.3234267
|View full text |Cite
|
Sign up to set email alerts
|

Feature Alignment FPN for Oriented Object Detection in Remote Sensing Images

Abstract: Annotating remote sensing images (RSIs) presents a notable challenge due to its labor-intensive nature. Semisupervised object detection (SSOD) methods tackle this issue by generating pseudo-labels for the unlabeled data, assuming that all classes found in the unlabeled dataset are also represented in the labeled data. However, real-world situations introduce the possibility of out-of-distribution (OOD) samples being mixed with in-distribution (ID) samples within the unlabeled dataset. In this paper, we delve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…However, the nearest neighbor interpolation upsampling still harms spatial information, resulting in poor network effect in details. Li et al [31] proposed a flow guided upsampling module, which utilizes a novel flow distortion to align features and achieve better cross scale fusion. Park and Paik [32] proposed a pyramid attention upsampling module for object detection by dividing the upsampling process into two branches to extract global contextual information and interpolate and scale feature maps, thereby reducing the loss of semantic information.…”
Section: Feature Upsamplingmentioning
confidence: 99%
“…However, the nearest neighbor interpolation upsampling still harms spatial information, resulting in poor network effect in details. Li et al [31] proposed a flow guided upsampling module, which utilizes a novel flow distortion to align features and achieve better cross scale fusion. Park and Paik [32] proposed a pyramid attention upsampling module for object detection by dividing the upsampling process into two branches to extract global contextual information and interpolate and scale feature maps, thereby reducing the loss of semantic information.…”
Section: Feature Upsamplingmentioning
confidence: 99%
“…In this work, we improve the TransMVSNet network, which uses a feature extraction module (FPN) [31] as its feature extraction network. In this paper, we use an asymptotic feature pyramid network (AFPN) [32] to support the direct interaction of non-adjacent layers.…”
Section: Related Work and Contributionmentioning
confidence: 99%
“…In conventional fusion methods, this leads to poor predictions of the boundaries between features. The accuracy of spatiotemporal data fusion depends largely on the accuracy of the input data, so an improved or innovative input data downscaling method can improve the performance of most spatio-temporal data fusion methods; for example, Zhai et al [21] and Xie et al [22] produced good results, and Li et al [23] proposed a MODIS strip noise cancellation strategy for spatio-temporal fusion methods, which better improves the accuracy of the fusion results. In addition, we found that compared to traditional spatio-temporal fusion methods, the deep learningbased spatio-temporal fusion algorithms bring more noise to the image fusion process and ignore the advantages of traditional spatio-temporal fusion algorithms in terms of image element unmixing and land use type change prediction.…”
Section: ⅰ Introductionmentioning
confidence: 99%